A QUANTITATIVE EVALUATION OF ACCOUNTING CURRICULA. - Noble, Paul L. (The Accounting Review, 1950)
Accountancy education, one of the newer fields of professional training, has developed rapidly in the United States in an effort to keep pace with the growth of the profession itself. If the accounting profession is to maintain its position of responsibility and respect, accountancy education must be maintained at a high level. The rapid growth of accountancy education in the past fifty years has resulted in a wide variety of types and levels of training. In 1945 there were at least 137 colleges and universities, recognized by state, regional, or national accrediting agencies, which had established schools of business. With the expanding scope of responsibilities of the accountant, the need is not for more accountants, but rather for more thorough and intensive preparation of those who do enter the profession. The State of New York has recognized the need for higher standards of professional preparation, when the requirement of graduation from an "approved" college was made a prerequisite to the CPA examination.